PENGARUH BUTIRAN FILLER KAYU SENGON TERHADAP KARAKTERISTIK PAPAN PARTIKEL YANG BERPENGUAT SERAT TANDAN KOSONG KELAPA SAWIT - Sunardi Sunardi; Moh. Fawaid; Rina Lusiana (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2017)
The waste of palm empty fruit bunches in Province Banten, especially Pandeglang and Lebak Region had been used optimally until today. The others hand, this waste to be environmental problem. This article will discuss the exploiting fiber of palm empty fruit bunches for reinforce the particle board. Composition and percentage of particle board consist of 15%  fiber, 15% epoxy resin, 20% PVAc and 50% wood sawdust. Specimens were made by cold press single punch method with pressure 30 bar. The particle board characteristics will observed is density, hardness, impact strength, elastic limit, deformation and micro structure. From this research was obtained that the particle board mesh 18 have the highest elastic limit and impact strength, that is 1157.86N/mm2 and 8.601kJ/m2, respectively. The deformation and density is 2.42% and 0.87gr/cm3, respectively.